Assessment of ground motion amplification in Taguig and Binondo from an artificial ground motion - Rodriguez, Rolando S. Jr; Victoria, Reymar Angelo R.
An artificial ground motion was simulated for a M7.2 West Valley Fault earthquake and synthetic ground motion records were generated for two sites - Taguig and Binondo. These sites were chosen due to the existing deep sedimentary layers which, according to studies, contribute to the amplification of ground motion as it propagate in the upper soil layers to the surface. The soil effects of the ground motion amplification were studied. Response spectra were also produced for both sites from the generated artificial motion. The software Extended Fault Simulation (EXSIM) was used to simulate the artificial ground motion using the stochastic finite-source approach. The software's accuracy is checked and then calibrated by comparing its results and the actual records with the 1999 M6.8 Hermana Mayor Earthquake and 1999 M7.6 Chi-Chi, Taiwan earthquake. Using EXSIM, the artificial ground motion was propagated from the source to the site at the specified depth of the soil layers. The Equivalent Earthquake Linear Response Analysis (EERA) program was then used to propagate the motion from the depth to the surface site passing through a user-defined soil profile (eg. borelogs), observing the site amplification effects. The results of the simulation show that for the Binondo site, ground amplification was observed, with 17% increase in maximum acceleration. A Fast-Fourier transform of the acceleration time history to frequency domain showed that the predominant frequency at the Binondo site is at 2Hz and 5Hz. From the generated response spectrum, the critical structure periods for the site was identified at 0.06s, 2s and 0.5s. For the Taguig site however, a deamplification of motion occurred, with 32% decrease in maximum acceleration. Further examination showed that it was due to the relatively soft soil at the site, and existing sand pockets beyond the 35m depth. These soft soil pockets caused significant damping of the maximum acceleration. However, this deamplification in Taguig may be treated as a special case due to the nature of the borehole source, near Laguna Lake which may be the reason for the soft soil and existing sand pockets. From the FFT of the generated motion, the predominant frequencies at the Taguig site was at 0.5 - 0.6Hz and 2-3Hz. The critical structure periods were at .15s to .4s, which was taken from the response spectrum at the site.